Analysis of Factors Influencing the Acceptance and Use of AdmApp at Cahaya Al-Qur’an Islamic Boarding School Using the UTAUT Model - Mulia Ningsih; Muhammad Romadhona Kusuma; Supriadi Panggabean; Ali Ahmad (Yayasan Mitra Peduli Indonesia, 2026)
The development of information technology encourages educational institutions to adopt digital solutions to improve administrative efficiency and service quality. This study aims to analyze the factors influencing the acceptance and use of Administration Application (AdmApp), a digital financial application implemented at Cahaya Al-Qur’an Islamic Boarding School, using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This quantitative study involved 29 staff respondents using a total sampling technique. Data were collected via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. The results show that Performance Expectancy (PE) significantly influences Behavioral Intention (BI) (β = 0.440; p = 0.006), Behavioral Intention significantly influences Use Behavior (UB) (β = 0.504; p = 0.000), and Facilitating Conditions (FC) significantly influence Use Behavior (UB) (β = 0.466; p = 0.000). Meanwhile, Effort Expectancy (EE) and Social Influence (SI) do not significantly influence Behavioral Intention. The research model explains 60.6% of the variance in Behavioral Intention and 83.2% of the variance in Use Behavior. Despite the limited sample size, the model demonstrates substantial explanatory power in understanding technology acceptance behavior. These findings indicate that perceived usefulness and the availability of technical support are important factors in the adoption of digital administrative systems in pesantren environments.